A Theology of Human Flourishing for Positive Psychology Pedagogy - Kapic, Kelly M. (Journal of psychology and christianity, 2023)
The article presents the discussion on Christian theology inform teaching positive psychology. Topics include Christian picture of flourishing has emerged, work remains to be done by Christians who seek to do interdisciplinary or integrative work on flourishing using Christian theology; and pedagogical implications of our conceptualization of flourishing for teaching positive psychology.